Protection motivation unmasked: Applying protection motivation theory to skepticism toward COVID-19 mask and vaccine mandates - Robin M. Kowalski; Kenzie Hurley; Nicholas Deas; Sophie Finnell; Kelly Evans; Chelsea Robbins; Andrew Cook; Emily Radovic; Hailey Carroll; Lyndsey Brewer; Gabriela Mochizuki (AIMS Press, 2022)
Variants of COVID-19 have sparked controversy regarding mask and/or vaccine mandates in some sectors of the country. Many people hold polarized opinions about such mandates, and it is uncertain what predicts attitudes towards these protective behavior mandates. Through a snow-ball sampling procedure of respondents on social media platforms, this study examined skepticism of 774 respondents toward these mandates as a function of the Protection Motivation Theory (PMT) of health. Hierarchical linear regressions examined Protection Motivation (PM) as a predictor of mask and vaccine mandate skepticism independently and with political party affiliation as a control. PM alone accounted for 76% of the variance in mask mandate skepticism, p < 0.001 and 65% in vaccine mandate skepticism, p < 0.001. When political affiliation was entered (accounting for 28% of the variance in mask mandate skepticism, p < 0.001, and 26% in vaccine mandate skepticism, p < 0.001), PM still accounted for significant percentages of variance in both mask (50%) and vaccine (43%) mandate skepticism, ps < 0.001. Across regressions, perceived severity, outcome efficaciousness, and self-efficacy each directly accounted for unique variance in mask and vaccine mandate skepticism, ps < 0.001; only perceived vulnerability failed to account for unique variance in the regressions, ps > 0.05. Specifically, the more severe participants perceived COVID-19 to be and the greater the perceived efficacy of masks and vaccines preventing the spread of COVID-19, the lower participants' skepticism toward mask and vaccine mandates. Similarly, the higher participants' self-efficacy in wearing masks or receiving the vaccine, the lower their skepticism toward mask and vaccine mandates.